Metal lithium battery

By using a lithium alloy negative electrode that combines structural phases and functional phases in metallic lithium batteries, the problems of uneven deposition and volume expansion of metallic lithium are solved, achieving long cycle and high-rate charge and discharge effects, and improving the battery cycle performance and energy density to meet the needs of low-altitude economies such as drones.

CN119361700APending Publication Date: 2025-01-24CHINA ENERGY LITHIUM
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411480655.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to realize long-cycle, large-scale charge and discharge metal lithium batteries in low-altitude economic applications such as drones, and there are problems such as uneven deposition of metal lithium, volume expansion, poor safety and poor circulation stability.

Method used

A lithium alloy anode with a specific composition is used, including a structural phase (such as lithium boron, lithium silicon or lithium tin) and a functional phase (such as an alloy formed by indium, tin, silver, bismuth, selenium, magnesium or antimony and lithium). Through the structural phase The interaction with functional phases regulates the deposition and stripping of metallic lithium, improving cycle performance and rate performance.

Benefits of technology

It has achieved good cycle performance, rate performance and safety of metal lithium batteries. It can be cycled more than 100 times at 0.5C/1C, and the cycle performance is improved by about 2 times. It also has high energy density and meets the high demand of the UAV market. Demand for specific energy, high rate and long cycle batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361700A_ABST
    Figure CN119361700A_ABST
Patent Text Reader

Abstract

The invention discloses a metal lithium battery. The metal lithium battery comprises a lithium alloy negative electrode and a positive electrode, the lithium alloy negative electrode comprises metal lithium and a lithium alloy distributed in the metal lithium, the lithium alloy comprises a structural phase and a functional phase, the structural phase comprises an alloy formed by elements boron, silicon or tin and lithium, and the functional phase comprises a functional phase. The functional phase comprises an alloy formed by lithium and at least one of indium, tin, silver, bismuth, selenium, magnesium or antimony. And the structural phase is used for stabilizing the structure of the negative electrode and relieving the volume expansion of the metal lithium. The functional phase reduces the surface potential energy of the negative electrode, regulates and controls the uniform deposition of metal lithium, and slows down the generation and growth of lithium dendrites. Compared with a lithium battery adopting a pure lithium strip, the cycle index of the lithium battery can be increased by about 2 times under 0.5 C / 1C, and the lithium battery has excellent cycle performance and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium batteries, and in particular to a metal lithium battery. Background Art

[0002] In recent years, with the rise and rapid development of low-altitude economy such as drones, people's demand for power batteries has also increased. Due to the large demand for power high-energy density batteries for products such as drones, traditional positive electrode materials such as lithium iron phosphate, lithium manganese oxide and lithium nickel cobalt aluminum oxide, combined with traditional negative electrode materials such as graphite and silicon-based materials, cannot meet actual needs, so a new battery system needs to be developed. Among them, metallic lithium, as the next generation of highly potential high-energy specific negative electrode materials, has attracted widespread attention.

[0003] However, although researchers have done a lot of preliminary basic work and studied various methods of modifying lithium metal and the relationship between structure and properties, they are still unable to overcome two or more of the problems such as volume effect, uneven deposition of lithium metal, poor safety and poor cycle stability at the same time in actual large-scale applications. Therefore, at this stage, few battery manufacturers can directly use lithium metal as a commercially viable negative electrode material, which seriously affects the promotion and development of lithium metal in practical application fields.

[0004] With the deepening of research, alloying can solve the above-mentioned problems of metallic lithium to a certain extent. For example, CN109244473A discloses a lithium alloy strip and a preparation method thereof, wherein the alloy strip contains a uniformly mixed metallic lithium element and a transition metal element with a micro-nano structure; the transition metal is at least one of copper, nickel, scandium, titanium, vanadium, chromium, manganese, cobalt and niobium, and the metallic lithium element is filled in the transition metal element with a mesh structure. The strength and hardness of the lithium alloy strip are better than those of metallic lithium, but the added transition metal has poor affinity for metallic lithium and cannot induce uniform deposition of metallic lithium.

[0005] Dongping Chen et al. prepared a Li-B-Zn ternary alloy by melting method (Dongping Chen, Piao Qing, Fengcheng Tang, et.al, A Self-Supported Hierarchic 3D Double Skeleton Host for Highly Stable Lithium Metal Batteries, Mater. Today Energy. (2023) 101272. DOI: 10.1016 / j.mtener.2023.101272.). Although the introduction of Zn improves the lithium affinity, the improvement on the diffusion of metallic lithium in the negative electrode is limited, and the rate performance is poor, which cannot meet the needs of the drone market.

[0006] In addition, there is little research on the matching of positive electrode indicators, electrolytes or solid electrolytes and metallic lithium in lithium batteries. If the matching is not appropriate, it is difficult for lithium batteries to fully exert their performance and advantages, resulting in problems such as short cycle life and poor rate performance.

[0007] Based on this, how to develop and design a metal lithium battery with a long cycle and high charge and discharge rate to meet the needs of low-altitude economy such as drones has become an urgent problem that needs to be solved. Summary of the invention

[0008] In order to solve the problems existing in the prior art, the present invention proposes a metal lithium battery, which simultaneously solves the problems of uneven deposition and volume expansion during the charging and discharging process of metal lithium, and has good safety and excellent cycle performance and rate performance.

[0009] The present invention provides a metal lithium battery, which comprises a lithium alloy negative electrode and a positive electrode; the lithium alloy negative electrode comprises metal lithium and a lithium alloy distributed in the metal lithium, the lithium alloy comprises a structural phase and a functional phase, the structural phase comprises an alloy formed by lithium and at least one of the elements boron, silicon or tin, the functional phase comprises an alloy formed by lithium and at least one of the elements indium, tin, silver, bismuth, selenium, magnesium or antimony, wherein when tin is included in the structural phase, the functional phase comprises an alloy formed by lithium and at least one of indium, silver, bismuth, selenium, magnesium or antimony; based on the mass of the lithium alloy negative electrode being 100%, the mass of the structural phase is ≤10% and the mass of the functional phase is ≤20%.

[0010] In the present invention, an alloy formed by boron, silicon or tin and lithium is used as a structural phase, which can not only release part of the lithium during the charging process and can be used as a negative electrode material, but also retain the structure of the alloy phase, playing a dual role of stabilizing the negative electrode structure of metal lithium and / or inducing uniform deposition of metal lithium. On the other hand, the Gibbs free energy of the functional phase reacting with metal lithium is low, which can reduce the deposition potential energy of metal lithium, and the atomic radius is large, which can significantly increase the diffusion rate of metal lithium in the functional phase, can quickly guide the deposition and diffusion of metal lithium, inhibit the generation and growth of lithium dendrites, and meet the needs of high-rate charging and discharging. The structural phase and the functional phase cooperate with each other to jointly regulate the deposition and stripping of metal lithium, improve the cycle performance and rate performance of the lithium battery; the specific quality selection of the structural phase and the functional phase makes the performance of the metal lithium battery meet the needs of the drone market for high specific energy, high rate and long cycle batteries.

[0011] In the present invention, the type of lithium alloy negative electrode can be lithium boron indium, lithium boron tin, lithium boron silver, lithium boron selenium, lithium boron bismuth, lithium boron magnesium, lithium tin silver, lithium tin selenium, lithium tin antimony, etc., including but not limited to the listed types.

[0012] In the present invention, the preparation method of the lithium alloy negative electrode is not specifically limited. For example, in an inert atmosphere such as argon, a lithium ingot is melted at 200°C or above to form liquid lithium, and then a material containing a structural phase and a functional phase is added, and the temperature is increased or not increased according to the melting condition of the material, and the temperature of the heating is preferably such that the materials are all in liquid state, and the materials are stirred, fully mixed, and kept warm, and then the temperature is naturally reduced or gradually reduced to form an alloy material, and finally the lithium alloy negative electrode is formed by mechanical rolling or coating.

[0013] Optionally, the structural phase includes elemental boron, which can form an alloy with metallic lithium. The lithium-boron alloy itself is a porous structure that can store lithium and functional phases, and can also provide space for the volume expansion of metallic lithium. In the discharge process, the lithium desorption potential is lower than that of metallic lithium, and the metallic lithium in the negative electrode is preferentially desorbed. The alloy plays a role in stabilizing the negative electrode structure. As the potential continues to increase, part of the lithium in the alloy is slowly desorbed, and part is not desorbed. The remaining alloy can serve as a skeleton to stabilize the negative electrode and alleviate the volume expansion problem of metallic lithium. During the charging process, the alloy phase can also play a role in regulating the deposition of metallic lithium.

[0014] Optionally, based on the mass of the lithium alloy negative electrode being 100%, the mass of the structural phase is

[0015] ≤10%, for example, it can be 0.1%, 0.5%, 1%, 2%, 3%, 5%, 8%, 9% or 10%, including but not limited to the listed point values. The mass of the structural phase is too low, and the effect of stabilizing the negative electrode structure is limited. The mass of the structural phase is too high, and more inactive substances are introduced, which is not conducive to obtaining a high specific energy lithium metal battery. The hardness of the lithium alloy is too high, and the processing performance is poor. Preferably it is 1-5%.

[0016] Optionally, the functional phase includes at least one of indium, tin, silver, bismuth, selenium, magnesium or antimony. The elements in the functional phase can better induce metal lithium deposition, and the atomic radius is larger than that of metal lithium, and the metal lithium diffuses faster, which is conducive to high-rate charge and discharge of metal lithium batteries.

[0017] Optionally, based on the mass of the lithium alloy negative electrode being 100%, the mass of the functional phase is

[0018] ≤20%, for example, it can be 0.1%, 0.5%, 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18% or 20%, including but not limited to the listed point values. The quality of the functional phase is too low, and the effect on the deposition regulation of metallic lithium is limited. The quality of the functional phase is too high, and more inactive substances are introduced, which is not conducive to obtaining a high specific energy lithium metal battery, and it is difficult to distribute evenly, which is not conducive to the coordination with the structural phase. The preferred range is 1-10%.

[0019] Optionally, the mass ratio of the structural phase to the functional phase is in the range of (0.05-50):1, for example, it can be 0.05:1, 0.08:1, 0.1:1, 0.15:1, 0.3:1, 0.5:1, 1:1, 2:1, 4:1, 5:1, 7:1, 10:1, 15:1, 20:1, 30:1, 40:1 or 5:1, including but not limited to the listed point values. If the mass ratio is too small and the structural phase is too small, the effect on the structural stability of the negative electrode and the uniform deposition and regulation of the storage functional phase and metallic lithium is limited; if the mass ratio is too large and the structural phase is too much, the processing performance of the negative electrode is deteriorated, and it is difficult to achieve below 50μm, and the energy density of the negative electrode is low, both of which do not meet the actual requirements of high specific energy batteries, and are preferably (0.1-10):1.

[0020] Optionally, the thickness of the lithium alloy negative electrode is 1-100 μm, preferably 5-50 μm.

[0021] Optionally, the positive electrode active material in the positive electrode includes at least one of lithium cobalt oxide, lithium manganese oxide, elemental sulfur, sulfided polyacrylonitrile, lithium iron phosphate, lithium iron manganese phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide or lithium-rich manganese base, preferably at least one of sulfided polyacrylonitrile, lithium nickel cobalt manganese oxide or lithium-rich manganese base.

[0022] Optionally, the surface density of the positive electrode is ≥15 mg / cm 2 , for example, it can be 15 mg / cm 2 ,

[0023] 18mg / cm 2 , 20mg / cm 2 , 25mg / cm 2 、30mg / cm 2 、35mg / cm 2 , 40mg / cm 2 , 45mg / cm 2 or 50mg / cm 2 Etc., including but not limited to the listed point values, preferably 20-50 mg / cm 2 .

[0024] Optionally, the surface capacity of the positive electrode is ≥2.85 mAh / cm 2 , for example, it can be 2.85 mAh / cm 2 、2.9mAh / cm 2 、3.0mAh / cm 2 、3.5mAh / cm 2 、4.0mAh / cm 2 、4.5mAh / cm 2 、5.0mAh / cm 2 、7.0mAh / cm2 、8.5mAh / cm 2 、9.0mAh / cm 2 、10.0mAh / cm 2 or 10.5mAh / cm 2 Etc., including but not limited to the listed point values, preferably 3.8-10.5 mAh / cm 2 .

[0025] Optionally, the ratio of the capacity of the lithium alloy negative electrode to the capacity of the positive electrode is ≤1.5, for example, it can be 1.5, 1.45, 1.4, 1.35, 1.3, 1.25, 1.2, 1.15, 1.1, 1.05, 1, 0.95, 0.9, 0.8 or 0.7, including but not limited to the listed point values. The ratio is one of the key parameters for obtaining a lithium metal battery with high specific energy, so that the metal lithium battery has excellent cycle performance and high specific energy, preferably 0.8-1.35.

[0026] Optionally, the metal lithium battery also includes an electrolyte, and the E / C ratio (ratio of the electrolyte injection volume to the battery capacity) of the metal lithium battery is ≤2, for example, it can be 2, 1.8, 1.5, 1.45, 1.4, 1.35, 1.3, 1.25, 1.2, 1.15, 1.1, 1.05, 1, 0.95, 0.9, 0.8, 0.7, etc., including but not limited to the listed point values. The E / C ratio is also one of the key parameters for obtaining a metal lithium battery with high specific energy, so that the metal lithium battery has excellent cycle performance and high specific energy, preferably 0.8-1.5.

[0027] In the present invention, the type of electrolyte is not specifically limited, and it can be an ether electrolyte or an ester electrolyte. As long as it is an electrolyte suitable for a metal lithium battery system, it belongs to the protection scope of the present invention.

[0028] Optionally, the test pressure of the metal lithium battery is ≤1.5N·m, for example, it can be 1.5, 1.45, 1.4, 1.35, 1.3, 1.25, 1.2, 1.15, 1.1, 1.05, 1, 0.95, 0.9, 0.8 or 0.7, including but not limited to the listed point values, preferably 0.5-1.2N·m. In the present invention, by adopting a specific type of lithium alloy negative electrode, the test pressure is minimized, and the test pressure is closer to the actual working condition, and the test pressure can be given by tools such as a torque wrench.

[0029] Optionally, the metal lithium battery includes at least one of a soft-pack metal lithium battery, a cylindrical metal lithium battery, or a button metal lithium battery. The metal lithium battery can be a laminated battery or a wound battery.

[0030] Compared with the prior art, the present invention has at least the following beneficial effects:

[0031] (1) The metal lithium battery provided by the present invention adopts a lithium alloy negative electrode of a specific composition. The structural phase in the lithium alloy negative electrode can solve the problem of volume expansion and / or uneven deposition of metal lithium, and has good cycle performance; the functional phase in the lithium alloy negative electrode can quickly guide the deposition and diffusion of metal lithium, inhibit the generation and growth of lithium dendrites, and meet the requirements of high-rate charge and discharge;

[0032] (2) The metal lithium battery provided by the present invention adopts a lithium alloy negative electrode of a specific composition, and the structural phase has a porous structure, which can store lithium and functional phase, and plays a good role in stabilizing the negative electrode; the structural phase and functional phase cooperate with each other to jointly improve the cycle performance, rate performance and safety of the metal lithium battery;

[0033] (3) The metal lithium battery provided by the present invention can be cycled more than 100 times at 0.5C / 1C by controlling key parameters such as the mass ratio of the structural phase and the functional phase in the lithium alloy, the ratio of the positive electrode capacity to the negative electrode capacity, and the E / C ratio. Compared with pure lithium strips and lithium alloys containing only structural phases or functional phases, the cycle performance is improved by about 2 times, and at the same time has a higher energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is the cycle test curve of the metal lithium battery in Example 1;

[0035] Figure 2 1 is the cycle test curve of Example 2, Example 4 and Example 5;

[0036] Figure 3 The cyclic test curves of Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown;

[0037] Figure 4 The following are the cycle test curves of Example 2 and Comparative Example 4. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical scheme and advantages of the present invention clearer, the features and other aspects of the present invention are described in more detail in conjunction with the embodiments. It should be understood that the described features and other aspects can be implemented in any suitable manner and in any suitable number combination without exceeding the scope of the present invention. Detailed features are mentioned in the specific embodiments to better understand the present invention, but it should be understood that these features are only used for explanation and not as a limitation on the scope of the invention. In addition, in order to better describe the present invention, the terms "including", "covering" and the like used herein should be understood in a broad sense without becoming the meaning of the terms. For ordinary technicians in this technical field, the specific meanings of the above terms in this application can be understood according to the specific circumstances. Unless otherwise specified, the directional words such as "upper", "lower", "left", "right" and the like used in this specification refer only to the relative orientation of an embodiment of the specification when it is used, and cannot be understood as an absolute limitation of the upper and lower, left and right, etc. of an embodiment of the specification. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings generally understood by ordinary technicians in the technical field to which the present invention belongs, and the illustrative meaning of the words is considered appropriate except for the explicit definition of the meaning different from that described in this specification.

[0039] Example 1

[0040] This embodiment provides a metal lithium battery, which includes a lithium boron indium negative electrode with a thickness of 100 μm, a mass fraction of boron of 1%, a mass fraction of indium of 10%, and a test surface capacity of 16.8 mAh / cm 2 , the surface capacity is 0.8 times the positive electrode capacity, Li 1.143 Ni 0.136 Co 0.136 Mn 0.544 O2 lithium-rich manganese-based material is the positive electrode, with a surface density of 50 mg / cm 2 The electrolyte was purchased from KLD-FS09 (1.0M LiFSI in FEC:DME=3:1vol%), the injection volume was 10g (E / C ratio was 2), and the capacity of the metal lithium battery was 5Ah. The charge and discharge test was carried out at a voltage range of 2.5-4.6V, 0.1C / 0.2C, and the test pressure was 1.5N·m.

[0041] The preparation method of the lithium-boron-indium negative electrode comprises the following steps: (1) in an argon environment, heating a lithium ingot in a heating furnace at 250° C. to melt it into liquid lithium, adding indium particles and boron powder while heating and stirring, raising the temperature to 600° C., and keeping the temperature for 10 hours until the indium particles and boron powder disappear, stopping heating, and slowly cooling to make an alloy ingot, and then using a mechanical rolling process and equipment to make a lithium-boron-indium negative electrode.

[0042] Under the condition of 25℃±2℃, the test is stopped when the capacity retention rate of the metal lithium battery is 80%. The test curve is as follows: Figure 1 As shown, from Figure 1 It can be seen that the metal lithium battery can be cycled 80 times and has good cycle stability. After calculation, the energy density of the metal lithium battery can reach 550wh / kg.

[0043] Example 2

[0044] This embodiment provides a metal lithium battery, which includes a lithium tin silver negative electrode with a thickness of 50 μm, a mass fraction of tin of 1%, a mass fraction of silver of 2%, and a test surface capacity of 9.8 mAh / cm 2 , the surface capacity is 1.5 times that of the positive electrode, LiNi 0.8 Co 0.1 Mn 0.1 L ternary material is the positive electrode, with a surface density of 20 mg / cm 2 The electrolyte was purchased from KLD-FS09 (1.0M LiFSI in FEC:DME=3:1vol%), the injection volume was 7.5g (E / C ratio was 1.5), and the capacity of the metal lithium battery was 5Ah. The charge and discharge test was carried out at a voltage range of 2.7-4.3V, 0.5C / 1C, and a test pressure of 1N·m. The energy density of the metal lithium battery can reach 419Wh / kg.

[0045] The preparation method of the lithium tin silver negative electrode comprises the following steps: (1) in an argon environment, heating a lithium ingot in a heating furnace at 300° C. to melt it into liquid lithium, adding silver particles while heating and stirring, the temperature rises to 650° C., and when the silver particles disappear, the temperature is kept for 4 hours, then tin particles are added, stirred until the particles disappear, and the temperature is kept for 8 hours, and then the heating is stopped and the temperature is gradually reduced, first the temperature is reduced to 500° C., and the temperature is kept for 2 hours, and then the temperature is reduced to 400° C., and the temperature is kept for 1 hour, and the cooling rate is 2° C. / min, to make an alloy ingot, and then the lithium tin silver negative electrode is made by using a mechanical rolling process and equipment.

[0046] Example 3

[0047] Compared with Example 2, the only difference is that the surface capacity of the negative electrode is 0.80 of the surface capacity of the positive electrode, and the other conditions remain unchanged.

[0048] Example 4

[0049] Compared with Example 2, the only difference is that the surface capacity of the negative electrode is 1.35 of the surface capacity of the positive electrode, and the other conditions remain unchanged.

[0050] Example 5

[0051] Compared with Example 2, the only difference is that the mass fraction of tin in the negative electrode is 5%, and the other conditions remain the same.

[0052] Example 6

[0053] Compared with Example 2, the only difference is that the mass fraction of tin in the negative electrode is 0.1%, and the other conditions remain the same.

[0054] Example 7

[0055] Compared with Example 2, the only difference is that the mass fraction of silver in the negative electrode is 0.1%, and the other conditions remain the same.

[0056] Example 8

[0057] Compared with Example 2, the only difference is that the mass fraction of silver in the negative electrode is 20%, and the other conditions remain the same. The energy density of the metal lithium battery is 403Wh / kg.

[0058] Example 9

[0059] Compared with Example 2, the only difference is that the injection amount is 6.25g (E / C ratio is 1.25), and the other conditions remain unchanged. The energy density of the metal lithium battery can reach 442Wh / kg. The injection amount of the metal lithium battery in Example 9 is reduced, and its cycle performance is worse than that of Example 2 (as shown in Table 1), but its energy density is greatly improved, and its performance is better than that of pure lithium strip or binary alloy (Comparative Examples 1-3). It is a metal lithium battery that takes into account both cycle and energy density.

[0060] Example 10

[0061] Compared with Example 2, the only difference is that the lithium tin silver negative electrode is replaced by a lithium boron silver negative electrode, and the other conditions remain unchanged.

[0062] Embodiment 11

[0063] Compared with Example 2, the only difference is that the lithium tin silver negative electrode is replaced by a lithium boron tin negative electrode, and the other conditions remain unchanged.

[0064] Example 12

[0065] Compared with Example 2, the only difference is that the lithium tin silver negative electrode is replaced by a lithium boron indium negative electrode, and the other conditions remain unchanged.

[0066] Example 13

[0067] Compared with Example 2, the only difference is that the lithium tin silver negative electrode is replaced by a lithium tin magnesium negative electrode, and the other conditions remain unchanged.

[0068] Embodiment 14

[0069] Compared with Example 2, the only difference is that the lithium tin silver negative electrode is replaced by a lithium silicon selenium negative electrode, and the other conditions remain unchanged.

[0070] Comparative Example 1

[0071] Compared with Example 2, the only difference is that the negative electrode is a pure lithium strip.

[0072] Comparative Example 2

[0073] Compared with Example 2, the only difference is that the negative electrode is a lithium-tin alloy, and the mass fraction of tin is 1%.

[0074] Comparative Example 3

[0075] Compared with Example 2, the only difference is that the negative electrode is a lithium-silver alloy, and the mass fraction of silver is 2%.

[0076] Comparative Example 4

[0077] Compared with Example 2, the only difference is that the negative electrode is a lithium-magnesium-silver alloy, the mass fraction of silver is 2%, and the mass fraction of magnesium is 1%.

[0078] Comparative Example 5

[0079] Compared with Example 12, the only difference is that the negative electrode is a lithium-boron-zinc alloy, and the other conditions remain unchanged. The preparation method adopts the method in the background technology.

[0080] Metal lithium battery performance characterization:

[0081] At 25°C±2°C, the metal lithium batteries of Examples 2-9 and Comparative Examples 1-3 were tested. The test was stopped when the battery discharge capacity decayed to 80% of the initial discharge capacity or the difference in discharge capacity between adjacent cycles was 5 mAh. The test data at 0.5C / 1C are shown in Table 1.

[0082] Table 1

[0083]

[0084]

[0085] From Table 1, we can see that:

[0086] (1) By comparing Examples 2 to 4, it can be seen that the cycle performance of the metal lithium battery in Example 4 is better than that in Examples 2 and 3. The test curves of Examples 2 and 4 are as follows: Figure 2 As shown, this is because the ratio of the surface capacity of the negative electrode to the positive electrode capacity in Example 4 is within the preferred range, which is beneficial to the performance of the metal lithium battery; although the number of cycles in Example 3 is worse than that in Example 2, the metal lithium battery still has both cycle performance and high specific energy.

[0087] (2) By comparing Example 2, Example 5 and Example 6, it can be seen that the cycle performance of the metal lithium battery in Example 5 is better than that in Example 2. The test curve is as follows: Figure 2 As shown, this is because the tin content as the structural phase in Example 5 is relatively high, which is beneficial to stabilizing the negative electrode structure and inducing uniform deposition of metallic lithium; the cycle performance of the metallic lithium battery in Example 6 is worse than that in Example 2, because the content of the lithium-tin alloy phase as the structural phase in Example 6 is relatively low, and the effect of stabilizing the negative electrode structure is limited.

[0088] (3) By comparing Example 2, Example 7 and Example 8, it can be seen that the cycle performance of the lithium metal battery in Example 7 is worse than that in Example 2. This is because the amount of silver as a functional phase is very small and has a limited effect on the deposition and regulation of lithium metal. The cycle performance and energy density of the lithium metal battery in Example 8 are lower than those in Example 2. This is because the content of the functional phase has an appropriate range and the more the better.

[0089] (4) By comparing Example 2 with Example 10 to Example 13, it can be seen that the cycle performance of the metal lithium battery in Example 10 is better than that in Example 2, which may be because the stability of the lithium boron silver negative electrode used in Example 10 is better than that of the lithium tin silver in Example 2; the cycle performance of the metal lithium battery in Example 11 is slightly worse than that in Example 2, which may be because the functional phase is a lithium tin alloy, and its regulating effect on metal lithium is worse than that of the functional phase lithium silver alloy in Example 2; the cycle performance of the metal lithium battery in Example 12 is better than that in Example 2, which may be because the structural phase in the lithium boron indium negative electrode is a lithium boron alloy, which has a porous structure, can store lithium and indium, and has a skeleton effect. The structural stability of the negative electrode is good, and it also has an inducing deposition effect on the deposition of metal lithium; the functional phase is a lithium indium alloy, which has a good lithium affinity effect and lithium diffusion ability, and has a good deposition regulation effect on metal lithium; the mutual cooperation of the structural phase and the functional phase improves the cycle performance better than that in Example 2; the cycle performance of the metal lithium battery in Example 13 is close to that in Example 2, which may be because the functional phase lithium magnesium alloy has a deposition regulation effect on metal lithium that is close to that of lithium silver alloy.

[0090] (5) By comparing Example 2 with Comparative Examples 1-3, it can be seen that the cycle performance of the metal lithium batteries in Comparative Examples 1-3 is worse than that in Example 2. This is because the pure lithium strip used in Comparative Example 1 has known defects such as volume expansion and the generation of lithium dendrites, which leads to rapid cycle decay. Figure 3 It can be seen (for the convenience of data comparison, some data are shown in Example 2, not all data), the difference between the discharge capacity of the 52nd cycle and the discharge capacity of the 53rd cycle of Comparative Example 1 is greater than 5 mAh, so the test is stopped; although there are structural phases or functional phases in the negative electrodes of Comparative Examples 2 and 3, the effect of solving the volume expansion of metallic lithium and / or the problem of lithium dendrites is not as good as that of the present invention; combined with Figure 3It can be seen that the difference in discharge capacity between two adjacent cycles of Comparative Examples 2 and 3 was greater than 5 mAh, so the test was stopped.

[0091] (6) By comparing Example 2 and Comparative Example 4, it can be seen that the cycle performance of the metal lithium battery in Comparative Example 4 is worse than that in Example 2. This is because although there are two alloy elements in Comparative Example 4, they cannot form the structural phase and functional phase of the present invention, and the cycle performance in Example 2 cannot be achieved under the same conditions.

[0092] (7) By comparing Examples 10-12 and Comparative Example 5, it can be seen that the cycle performance of the metal lithium battery in Comparative Example 5 is worse than that in Examples 10-12. This is because the functional phase used in Comparative Example 5 is not within the scope of the present invention, and the regulation and diffusion capabilities of the functional phase on metal lithium are not as good as those in Example 12.

Claims

1. A metal lithium battery, characterized in that: The metal lithium battery comprises a lithium alloy negative electrode and a positive electrode; the lithium alloy negative electrode comprises metal lithium and a lithium alloy distributed in the metal lithium, the lithium alloy comprises a structural phase and a functional phase, the structural phase comprises an alloy formed by lithium and at least one of the elements boron, silicon or tin, the functional phase comprises an alloy formed by lithium and at least one of the elements indium, tin, silver, bismuth, selenium, magnesium or antimony, wherein when the structural phase comprises tin, the functional phase comprises an alloy formed by lithium and at least one of indium, silver, bismuth, selenium, magnesium or antimony; Taking the mass of the lithium alloy negative electrode as 100%, the mass of the structural phase is ≤10% and the mass of the functional phase is ≤20%.

2. The metal lithium battery according to claim 1, characterized in that: Taking the mass of the lithium alloy negative electrode as 100%, the mass of the structural phase is 1-5%.

3. The metal lithium battery according to claim 1 or 2, characterized in that: Taking the mass of the lithium alloy negative electrode as 100%, the mass of the functional phase is 1-10%.

4. The metal lithium battery according to any one of claims 1 to 3, characterized in that: The mass ratio of the structural phase to the functional phase is in the range of (0.05-50):1, preferably (0.1-10):

1.

5. The metal lithium battery according to any one of claims 1 to 4, characterized in that: The thickness of the lithium alloy negative electrode is 1-100 μm, preferably 5-50 μm.

6. The metal lithium battery according to any one of claims 1 to 5, characterized in that: The positive electrode includes at least one positive electrode active material selected from lithium cobalt oxide, lithium manganese oxide, elemental sulfur, sulfided polyacrylonitrile, lithium iron phosphate, lithium iron manganese phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide or lithium-rich manganese-based. Preferably, the positive electrode active material is at least one of sulfided polyacrylonitrile, lithium nickel cobalt manganese oxide or lithium-rich manganese-based.

7. The metal lithium battery according to any one of claims 1 to 6, characterized in that: The surface density of the positive electrode is ≥15 mg / cm 2 , preferably 20-50 mg / cm 2 ; Preferably, the surface capacity of the positive electrode is ≥2.85 mAh / cm 2 , preferably 3.8-10.5 mAh / cm 2 .

8. The metal lithium battery according to any one of claims 1 to 7, characterized in that: The ratio of the capacity of the lithium alloy negative electrode to the capacity of the positive electrode is ≤1.5, preferably 0.8-1.

35.

9. The metal lithium battery according to any one of claims 1 to 8, characterized in that: The metal lithium battery also includes an electrolyte, and the E / C ratio of the metal lithium battery is ≤2, preferably 0.8-1.

5.

10. The metal lithium battery according to any one of claims 1 to 9, characterized in that: The metal lithium battery includes at least one of a soft-pack metal lithium battery, a cylindrical metal lithium battery or a button metal lithium battery.

Citation Information

Patent Citations

  • A lithium alloy strip and a preparation method thereof

    CN109244473A